Trayectoria tecnológica de los mercados eléctricos en Centroamérica - Vargas-Alfaro, Leiner (2015)
This article presents a characterization of the institutional forms of the electricity market in Central America at least three different models: Guatemala, El Salvador and Costa Rica; as well as the impact on the technological trajectory. This is important not only for path dependence and technological concentration of countries with respect to energy (electricity and fuel) based on fossil fuels; but also, by the impact and vulnerability that under climate change situation this trajectory has a highest concentration an d dependence "stickiness" of these fuels based electricity generation technologies as well as dirty transportation activities. We showed a shift towards electricity sources based on fossil fuels in countries that pushed for market reforms with shortterm incentives